Foliar phosphorus fractions reveal how tropical plants maintain photosynthetic rates despite low soil phosphorus availability. (24th January 2019) - Mo, Qifeng; Li, Zhi'an; Sayer, Emma J.; Lambers, Hans; Li, Yingwen; Zou, Bi; Tang, Jianwu; Heskel, Mary; Ding, Yongzhen; Wang, Faming
Abstract: Nitrogen (N) and phosphorus (P) are essential nutrients for plant metabolism, and their availability often limits primary productivity. Whereas the effects of N availability on photosynthetic capacity are well established, we still know relatively little about the effects of P availability at a foliar level, especially in P‐limited tropical forests. We examined photosynthetic capacity, leaf mass per area (LMA) and foliar P fractions in five woody plant species after 6 years of N and P fertilization in a lowland tropical forest. Foliar N:P ratios indicated P limitation of the unfertilized plants; accordingly, photosynthetic P‐use efficiency (PPUE) and LMA decreased with P addition, and foliar N and P concentrations increased, whereas N addition had little effect on measured foliar traits. However, P addition enhanced photosynthetic capacity only in one species and not in other four species. We then assessed plant acclimation to low P availability by quantifying four fractions of foliar P representing different functional pools: structural P, metabolic P (including inorganic P), nucleic acid P, and residual P. We found that P addition enhanced the concentrations of metabolic, structural, and nucleic acid P fractions in all species, but the magnitude of the effect was species‐specific. Our findings indicate that tropical species acclimate to low P availability by altering allocation of foliar P to meet the demand of P for photosynthesis. Importantly, species typical of lowland tropical forests in East Asia maintained their photosynthetic rate under low P availability. We conclude that P limitation of leaf photosynthetic capacity may not be as common as previously assumed due to plant acclimation mechanisms in low‐P tropical forests. Species‐specific strategies to allocate P to different foliar fractions represent a potentially important adaptive mechanism for plants in P‐limited systems. Abstract : Plain Language Summary Abstract : 氮和磷是植物代谢过程中的重要养分也是限制生态系统初级生产力的主要因子。尽管我们对氮如何影响植物光合能力有了比较全面的认识，但在低磷的热带森林中，我们对土壤磷如何影响植物光合功能还缺乏系统的了解。本研究通过在热带森林的野外氮磷添加实验中测定不同植物的叶片光合能力和叶片功能性状以及叶片磷组分，系统的了解了这些植物在叶片尺度上的低磷环境的适应机制。叶片氮磷比的结果表明该森林是磷限制的生态系统，施磷降低了叶片磷利用效率和比叶重但增加了叶片磷和氮的浓度，而施氮对叶片性状无显著影响。施磷仅增加了一个广布种的叶片光合能力而对其他四个狭布种无显著影响。我们进一步了解了叶片磷组分的变化，发现施磷处理增加了所有物种的代谢磷、结构磷和核酸磷组分，但其增加的尺度因种而异。这些结果表明热带森林植物通过改变叶片中磷的分布来满足光合作用对磷的需求，并且东亚地区的热带森林的典型植物能够在低磷的土壤环境中维持相对稳定的光合速率。通过该项研究，我们认为由于热带植物进化的适应机制，低磷对热带森林植物的光合能力的限制比预想的要小的多。不同植物的叶片磷组分的分配策略是其重要的对低磷环境的适应机制。 A plain language summary is available for this article.